The influence of beta-adrenoceptor blocking drugs with and without intrinsic sympathomimetic activity on the hormonal responses to hypo- and hyperglycaemia. - Schlüter, K J (1982)
1 The effects of oral doses of pindolol (15 mg), metoprolol (200 mg) and propranolol (160 mg) on the response to insulin-induced hypoglycaemia and an oral glucose load were investigated. 2 Serum insulin and serum C-peptide secretion in response to a glucose load were inhibited (2P less than 0.01) by metoprolol and propranolol but not by pindolol. 3 During hypoglycaemia metoprolol and propranolol inhibited the clearance of insulin (2P less than 0.01) and caused a delay of glucose nadirs. 4 Adrenaline secretion during hypoglycaemia was markedly increased by metoprolol and propranolol but not by pindolol. 5 The counterregulatory response of growth hormone, ACTH and cortisol was increased following metoprolol and propranolol but not after pindolol. 6 The hypoglycaemic symptoms and signs showed a prevalence of sweating and prolonged changes in skin conductivity whereas palpitations were not observed during beta-adrenoceptor blockade. Asymptomatic hypoglycaemia did not occur. 7 The absence of unphysiological rises in adrenaline, growth hormone, ACTH and cortisol supports the use of a beta-adrenoceptor blocker with intrinsic sympathomimetic activity.